ANALYSIS OF THE EFFECT OF FINANCIAL RATIO ON STOCK PRICES WITH GROWTH OPPORTUNITY AS A MODERATING VARIABLE IN RETAIL TRADE SECTOR COMPANIES IN INDONESIA STOCK EXCHANGE - Affandi, Muhammad Rispan (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study is to examine the effect of the Working Capital to Total Asset (WCTA) ratio, Retained Earning to Total Assets (RETA), Earning Before Interest and Tax to Total Assets (EBITTA), and Total Assets Turn Over (TATO) partially and simultaneously to stock prices with Growth Opportunity as a moderating variable. The population of this research is 26 retail companies listed on the Indonesia Stock Exchange with observations from 2013 to 2017. This study uses saturated sampling. The analytical tool used is panel data regression and data processing using software Eviews 7. The results of this test show that the WCTA and RETA ratios partially have no significant effect while the EBITTA and TATO ratios have a significant effect on stock prices. The simultaneous ratio of WCTA, RETA, EBITTA, TATO has a significant effect on stock prices. Growth Opportunity can moderate the relationship between the ratio of WCTA, RETA, EBITTA to stock prices but cannot moderate the Total Assets Turn Over (TATO) on stock prices.